Perancangan Sistem Terintegrasi untuk Otomatisasi Perhitungan PPh Pasal 21 - Muhammad Jeasen Allan Budy Kusuma; Diah Armeliza; Tresno Eka Jaya (Jurnal Akuntansi, Perpajakan dan Auditing, 2026)
This study aims to design an integrated Microsoft Excel-based system for automating Article 21 Income Tax calculations at PT XYZ. The problem addressed is the difference between internal company calculations and tax consultant calculations due to unintegrated spreadsheets, inconsistent input data, and manual reconciliation. This study applies a Research and Development method using the System Development Life Cycle with a Waterfall model. Data were collected through observation, interviews, and documentation of payroll and tax processing activities. The result is an integrated Excel system containing employee data, income components, deductions, PTKP status, effective tax rate tables, monthly calculations, annual recapitulation, 1721-A1 support, and CSV reporting output for Coretax DJP import. The system improves calculation consistency, supports annual reconciliation, reduces input errors, and prepares structured tax reporting data.